ANTARA BIOGRAFI DAN HISTORIOGRAFI (Studi 36 Buku Biografi di Indonesia ) - Daud, Safari (Analisis: Jurnal Studi Keislaman, 2013)
The writing of the religious leaders in Indonesia ranks the second after  political  figures ones. This ranking  is the  result  of Gerry van Klinken’ research on biographies writings in Indonesia from1950 to 2000 as many as 2,629 books . As the domain of science history , the quantity  of writing biographies have not shown the quality  of  historiography.  A total  of  36  biography  books  that the writer  analyzed  using prevalence  history  method  found out four historiographical  issues. First, in the writing  of character’s biography about his life has an impact on a critical attitude  gap between academic interests of biographer and psychological pressure from mainstream figures who has written. Second, there is a plurality  of the  biographer  rated  from reporter,  historians, scholars and experts from various professions with their own characteristics of literacy. Third, a biography written by historian is  more  scientific  which  shows  the  portion  of  the  balance  in the  selection  of figures,  while the  non- historian  biographer  is more interested  in contemporary  issues and prefer well-known figures. A variety  of professions  of the  biographer  is one of a consequences of the biography writing that much or even related to historiography.